2018
DOI: 10.1002/hep.30234
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of Serum Matrix Metalloproteinase‐7 for Biliary Atresia

Abstract: The diagnosis of biliary atresia (BA) remains a clinical challenge because affected infants have signs, symptoms, and serum liver biochemistry that are also seen in those with other causes of neonatal cholestasis (non-BA). However, an early diagnosis and prompt surgical treatment are required to improve clinical outcome. Recently, the relative abundance of serum matrix metalloproteinase-7 (MMP-7) was suggested to have discriminatory features for infants with BA. To test the hypothesis that elevated serum conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
122
4
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 114 publications
(131 citation statements)
references
References 17 publications
4
122
4
1
Order By: Relevance
“…[5,8] γ-GT levels were higher in infants with BA than in non-BA controls in our study, consistent with the results of other reports. [5,26] γ-GT or stool color did not show good diagnostic ability in our study; however, the novel and most relevant finding of our study was that a combination of γ-GT, clay stool, and GCDCA/CDCA ratio overall improved the diagnostic performance of the tests. Besides, in our study, 29 (85.3%) BA patients had a positive HBS, which was defined as the absence of the radiotracer in the intestines for up to 24 h. However, 3 (14.7%) cases of BA showed negative HBS results, which means the radiotracer could be seen in the intestines for up to 24 h. Since BA is a progressive inflammatory cholangiopathy, and only 20% of BA patients showed complete fibroinflammatory obliteration.…”
Section: Discussioncontrasting
confidence: 67%
“…[5,8] γ-GT levels were higher in infants with BA than in non-BA controls in our study, consistent with the results of other reports. [5,26] γ-GT or stool color did not show good diagnostic ability in our study; however, the novel and most relevant finding of our study was that a combination of γ-GT, clay stool, and GCDCA/CDCA ratio overall improved the diagnostic performance of the tests. Besides, in our study, 29 (85.3%) BA patients had a positive HBS, which was defined as the absence of the radiotracer in the intestines for up to 24 h. However, 3 (14.7%) cases of BA showed negative HBS results, which means the radiotracer could be seen in the intestines for up to 24 h. Since BA is a progressive inflammatory cholangiopathy, and only 20% of BA patients showed complete fibroinflammatory obliteration.…”
Section: Discussioncontrasting
confidence: 67%
“…A recent study used proteomics to screen sera from infants with BA and showed a strong positive correlation to elevated levels of MMP‐7 and gamma‐glutamyltransferase. The MMP‐7 level is being used as a diagnostic biomarker for BA as initial findings were further confirmed by another study . Immunohistochemistry of liver samples with BA showed increased presence of MMP‐7 in extrahepatic bile duct cholangiocytes .…”
Section: Discussionmentioning
confidence: 73%
“…The MMP-7 level is being used as a diagnostic biomarker for BA as initial findings were further confirmed by another study. (47) Immunohistochemistry of liver samples with BA showed increased presence of MMP-7 in extrahepatic bile duct cholangiocytes. (46) MMP-7 gene expression was also increased in the liver, and levels increased in intrahepatic cholangiocytes of patients with BA.…”
Section: Discussionmentioning
confidence: 96%
“…In contrast, an optimal serum MMP-7 level of >52.85 ng/mL was derived in a previous study. 7 Clinicians can solve this problem by ensuring that individual reference intervals are derived for each of the various MMP-7 enzyme-linked immunosorbent assay kits. Once this is done, clinicians can choose to capitalize on the utility of serum MMP-7 measurements as demonstrated in this work, to potentially address some of the difficult challenges when managing patients with biliary atresia.…”
Section: Mmp-7mentioning
confidence: 99%
“…4,5 In 2 breakthrough studies, serum MMP-7 levels at diagnosis were significantly higher in patients with biliary atresia compared with cholestatic patients who did not have biliary atresia. 6,7 These findings raised the exciting possibility that a simple MMP-7 blood test could help diagnose biliary atresia, potentially in place of the more expensive and invasive testing currently used.…”
mentioning
confidence: 99%